Validation of a simple and rapid HPLC-UV method for simultaneous analysis of co-delivered doxorubicin and verapamil and its application to characterization of PLGA nanoparticles - Maryam Kazemi; Fatemeh Ahmadi; Mozhdeh Piltan; Shohre Alipour (Shiraz University of Medical Sciences, 2022)
To overcome developing drug resistance in cancer treatment, combination therapy could be an attractive strategy. It has been shown that doxorubicin anti-cancer properties are improved by P-glycoprotein inhibitors such as verapamil. Polymeric nanoparticles (NPs) of poly lactic-co-glycolic acid (PLGA) can simultaneously deliver verapamil and doxorubicin and provide an effective anti-cancer drug delivery system. The present study aimed to develop an efficient high performance liquid chromatography (HPLC) method for the simultaneous determination of doxorubicin and verapamil encapsulated in PLGA nanoparticles (NPs). Quantification of doxorubicin and verapamil was performed by the HPLC method. The method was developed by evaluating combination of different solvents ratios as mobile phase and modification of the mobile phase rate. A series of doxorubicin and verapamil solutions at concentrations of "6.25, 12.5, 25, 50, and 100 μg/ml" and "0.625, 1.25, 2.5 and 5 μg/ml" were prepared, respectively. The method was validated by calculating selectivity, linearity, accuracy, intra- and inter-day precision. The validated method was used to characterize prepared doxorubicin-verapamil PLGA NPs by determination of drug loading, encapsulation efficiency% and in vitro release. Results indicated that analysis method was selective with notable separation efficiency and acceptable limit of detection and limit of quantification which shows the sensitivity of the method. The linear standard curve with suitable accuracy and precision confirms the validation of method for simultaneous analysis of doxorubicin and verapamil in NPs.   Please cite this article as: Maryam Kazemi, Fatemeh Ahmadi, Mozhdeh piltan, Shohreh Alipour. Validation of a simple and rapid HPLC-UV method for simultaneous analysis of co-delivered doxorubicin and verapamil and its application to characterization of PLGA nanoparticles. Trends in Pharmaceutical Sciences. 2022;8(4):223-232. doi: 10.30476/TIPS.2022.95526.1149